Australian Law School Libraries: A Position Statement and Standards - Jacqueline Elliott (Legal Education Review)
There is a certain sense of “deja vu” about this publication. It deals again with issues that have been discussed for over 20 years. At least in the first section, much of it has been said before — in the ALTA Report 1974, the Pearce Report 1987. In 1994 increasing concern at the running down of university law libraries prompted a feeling that the law schools “need to establish benchmarks” to prevent further reductions to Australian universities’ collections of legal material. This publication is the result. The 52 page book is presented in two parts: “Law libraries, law teaching and legal research”, a position statement by the Committee of Australian Law Deans (20 pages), and “Australasian Universities Law Library Standards 25 August 1995” (32 pages). The whole is a positive effort on the part of law deans and law librarians to explain the need and to establish standards for law school libraries. Clearly it is an attempt to stop the damage caused by continual cancelling of highly valued serial and monograph holdings, damage which has been going on since the seventies. There is a limit to what a law school needs in its library to function effectively. This is an attempt at a definitive statement not only on what standard is required for minimum law holdings but also for staffing, equipment, technical services, etc.